Celebration of the 400th anniversary of the Lithuanian book - Vladas Žukas (Knygotyra)
In 1947, Lithuania celebrated the 400th anniversary of the first Lithuanian book, M. Mažvydas's Cathechismus, published in 1547. During this celebration, scientific conferences and book exhibitions were organized, and several significant works devoted to the anniversary were published.